INNOVATION IN CAPITALIST ECONOMIES crises, challenges and opportunities. - Ülgen, Faruk, 1963-; Klapkiv, Lyubov (Routledge frontiers of political economy., 2025)
Innovation is critical to increasing global prosperity and also essential to surviving and overcoming the ongoing challenges of pandemics, wars, climate change, and systemic financial turmoil. At the same time, major corporations seek to transform new knowledge and scientific progress into profitable innovations and to increase their influence over society. But if, as these firms claim, this tremendous innovativeness has a positive long-term effect on our lives, who ultimately pays the price for this development? This edited volume tackles issues related to innovation dynamics of modern capitalist economies, exploring the nature, the effects and the dynamics of innovative behaviour and the social impact of related policies. The first part of the book includes chapters on the selected drivers of innovative changes that driven by companies. The focus is made on organizational and financial determinants of innovations as well as on creative communities and social cooperation in networks that promote creative decisions. The second part is devoted to the innovations that play a role in the creation of added value and new financial solutions that allow companies to keep their vitality under the pressure of multiple events such a pandemic, climate policies, or growing geopolitical risk. Together, the contributors explore the various impacts of innovation on the way we are organizing capitalist economies in the 21st century. This book will be of great interest to readers of the political economy of financial and economic development, innovation, banking and finance studies, economic policy, and economic crises.